2010
DOI: 10.1089/sur.2009.013
|View full text |Cite
|
Sign up to set email alerts
|

The Grade–Response Relation between Severity of Peritonitis and Serum Cytokine Concentrations Explains Mannheim Peritonitis Index Threshold

Abstract: Around the mean value of grade II peritonitis, the equilibrium between pro-inflammatory and anti-inflammatory cytokines is lost. This change coincides with the 26-point threshold for the MPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Reports on any association of APACHE II scores and mortality remain controversial. 13,32,[36][37][38] In our study, we found higher mortality among patients with APACHE II scores .11.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Reports on any association of APACHE II scores and mortality remain controversial. 13,32,[36][37][38] In our study, we found higher mortality among patients with APACHE II scores .11.…”
Section: Discussionsupporting
confidence: 51%
“…This result was consistent with other reports. 12,[27][28][29] Bracho-Riquelme and colleagues 13 reported that MPI scores greater 26 were associated with increased mortality. In our series, we also found significantly increased mortality in association with MPI scores over 26.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a simple scoring system, widely used, and is specific to peritonitis. With this index, the grade-response relation between severity of peritonitis and the concentration of key regulatory serum cytokines has been demonstrated [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…17 Moreover, a series of cytokines related to SIRS, including CRP, TNF-α and IL-6, which are also called proinflammatory factors are blamed for the process of BT. 18…”
Section: Discussionmentioning
confidence: 99%